IXDB : towards click-pinch-drag-enter XML databases - Boh, Ze Yang. (2013)
Traditional search engines use keywords to search and are usually limited by how the query is performed. Users who seek meaningful results are often faced with an overload of information due to the huge amount of data returned, most of which are useless or irrelevant. Through the use of complex SQL queries, one can help to filter out information that are not useful.